SULAâS REBELLION AGAINST THE BLACK CONVENTIONAL VALUES AS THE INDICATOR OF HER FEMINIST SPIRIT IN TONI MORRISONâS SULA - Rosdiana, Laily; Basuki, Imam; Cahyawati, Erna (Publika Budaya, 2014)
Sula a novel written by Toni Morrison tells about a black woman who rebel against the patriarchal system, racial oppression and class discrimination as the conventional values in Bottom society, where the blacks live.This thesis focuses on Sulaâs Rebellion against the black conventional values as the indicator of her feminist spirit in Toni Morrisonâs Sula. Sula as the main female character breaks and rebels the conventional values surrounding her. The strongest influential factors that shape and influence Sulaâs rebellion are coming from the society, family and friendship. She breaks the patriarchal culture and the racial problems within her society by rejecting marriage and having free sexual partner. For those reasons, Sula is named a pariah and evil. The research employs Marxism and Afro-American Feminism to discuss the dominant ideology of whites, classes, and racialism in the world of black feminism. The research is qualitative research which applies text in Sula as the basic data. The data are analyzed to show the reason of Sulas rebellion in rejecting marriage and having free sexual life. The data reveals that black women face double oppression such as patriarchy and racialism. Therefore, the study is significant to understand Afro-American women and their struggle against oppression of patriarchal system and racial problems in their society. Keywords: Rebellion, Conventional Values, Afro American Feminism, Racialism, consciousness, Patriarchy, Class discriminations, Pariah